Ugotavljanje razvitosti povezovalnega odnosa organizacije z dobavitelji - modelski pristop na primeru vzorca organizacij v Sloveniji - Iršič, Matjaž (Akademija MM, 1999)
In the present paper we are dealing with the problem of the development of organisational relationship with its supplier in the purchasing market. The level of relationship with supplier is one of the most significant elements in the context of study of the developed concept of relationship marketing. During the research process we are investigating the level of development of the relationship on the sample of Slovenian enterprises using "Olsen-Elram" modelling multifactor approach with two important dimensions: relative atractiveness of the supplier and intensity of the relationship. On the base of weighted estimation we have found out, that the level of development of such relationship in the Slovenian enterprises is relatively low.
Keywords: corporation; marketing; nabava; nabavna politika; podjetje; purchasing; trženje